CaixaForum Zaragoza - Pinós, Carme; Brufau, Robert (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
I like my buildings to be a structural expression. Even the designs of furniture we produce in the studio are pure structure. They minimise gestures based on the logic of strength, stability and support.